Pengaruh Disiplin dan Motivasi Kerja Terhadap Prestasi Kerja Karyawan di Pabrik Gula Ngadiredjo Kediri - Mukhlisotul Istiana (BIMA : Journal of Business and Innovation Management, 2019)
This study aims to analyze the influence of Discipline and Work Motivation on Employee Performance in the Ngadiredjo Kediri Sugar Factory by using research technique of quantitative data analysis and research methods of causal with data through surveys and distributing the questionnaires to 157 employees of the Nngadiredjo Kediri Sugar Factory using random sampling, namely interpretation the members of sample from the population are taken randomly without regard to the strata in that population. The technique of data analysis is using the Linear Regression of the tuned. The results of this hypothesis study showed the results that (1) Partial Discipline affects employee performance in Ngadiredjo Kediri Sugar Factory, (2) Work motivation partially influences Employee Job Performance in Ngadiredjo Kediri Sugar Factory, (3) Discipline and Work Motivation have Simultaneous influence on Employee Job Performance in Ngadiredjo Kediri Sugar Factory.